2021
DOI: 10.1186/s12960-021-00573-4
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and doctor emigration: the case of Ireland

Abstract: Background Since the 2008 recession, Ireland has experienced large-scale doctor emigration. This paper seeks to ascertain whether (and how) the COVID-19 pandemic might disrupt or reinforce existing patterns of doctor emigration. Method This paper draws on qualitative interviews with 31 hospital doctors in Ireland, undertaken in June–July 2020. As the researchers were subject to a government mandated work-from-home order at that time, they utilised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…The establishment of writing teams also ensured that co-authors (academics and clinicians with other work commitments) did not become over-burdened. Three open access articles were published between February and July 2021 (Byrne et al, 2021); Creese, Byrne, Conway, et al, 2021; Humphries, Creese, Byrne, & Connell, 2021, along with three research briefs (see https://www.rcpi.ie/hdrm/) which were circulated and discussed with key policy makers. Two opinion pieces were published in early 2021 to further raise the profile of the research project and disseminate findings (Humphries, 2021; Humphries et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The establishment of writing teams also ensured that co-authors (academics and clinicians with other work commitments) did not become over-burdened. Three open access articles were published between February and July 2021 (Byrne et al, 2021); Creese, Byrne, Conway, et al, 2021; Humphries, Creese, Byrne, & Connell, 2021, along with three research briefs (see https://www.rcpi.ie/hdrm/) which were circulated and discussed with key policy makers. Two opinion pieces were published in early 2021 to further raise the profile of the research project and disseminate findings (Humphries, 2021; Humphries et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…7 Humphries et al report little change in 2020 in the factors that were pushing Irish doctors to leave, from the perspective of NCHDs who returned to Ireland to support the COVID-19 response, and that of other NCHDs who were contemplating leaving. 21 The authors state that "the pandemic intensified and reinforced, rather than radically altered, the dynamics of doctor emigration from Ireland. " Between 2019 and 2020, there was no change in the 4% of consultants in unapproved posts, nor in the 6%-7% of working consultants not registered on the specialist division register of the Medical Council.…”
Section: Covid-19 -Impact and Opportunitymentioning
confidence: 99%
“…7 However, over 40% of the increase in trainees (261/629) were interns, ie, medical graduates undertaking their first, pre-registration year of training; and “This increase is for one year only, as a direct result of the COVID-19 pandemic.” 7 Humphries et al report little change in 2020 in the factors that were pushing Irish doctors to leave, from the perspective of NCHDs who returned to Ireland to support the COVID-19 response, and that of other NCHDs who were contemplating leaving. 21 The authors state that “the pandemic intensified and reinforced, rather than radically altered, the dynamics of doctor emigration from Ireland.” Between 2019 and 2020, there was no change in the 4% of consultants in unapproved posts, nor in the 6%-7% of working consultants not registered on the specialist division register of the Medical Council. 7 Most are consultants who have not completed specialist training, almost all of whom work in smaller hospitals, raising serious questions about the quality of care provided to rural populations.…”
Section: Covid-19 – Impact and Opportunitymentioning
confidence: 99%
“…Furthermore, this author gives a deepening analysis of Irich doctors' emigration and notes that reasons for leaving of young doctors include: unsatisfactory working conditions, lack of supervision and mentoring, and their comparatively poor training experiences. Additionally, the study of Humphries et al (2021) done with qualitative interviews on a sample of 31 hospital doctors in Ireland has shown that the pandemic intensified and reinforced, rather than radically altered, the dynamics of doctor emigration from Ireland. They also argue that "persistent emigration is usually the symptom, not the cause, of an underlying problem and is the result of a range of interacting factors which each exacerbate the other" (p. 7).…”
Section: Previous Research and Healthcare Sector In North Macedoniamentioning
confidence: 99%
“…Stuart et al (2021). Humphries et al (2021) have noted that "the pandemic intensified and reinforced, rather than radically altered, the dynamics of doctor emigration from Ireland", while Jamebozorgi et al (2021) and Rangachari and Woods (2020) are more focused on strategies and recommendations for staff retention. Nevertheless, this crisis showed that the retention of the most skillful staff should be a central aim of every organization, especially in the healthcare sector.…”
Section: Previous Research and Healthcare Sector In North Macedoniamentioning
confidence: 99%